Paytech as a Segment of Cashless Payments in Poland – Status and Development Prospects - Król, Patryk Janusz; Starzycki, Tomasz (Journal of Finance and Financial Law, 2024)
The purpose of the article. The article aims to present the state of development of the PayTech sector in Poland and analyze the prospects for its development. The authors examine whether the Polish PayTech sector is sufficiently developed to expand to the entire European Union, also identifying alternative directions of development and obstacles to the expansion of Polish payment systems, mainly the BLIK system. Methodology. The methodology of the article is based on the analysis of the literature on the subject, mainly based on research available in the Google Scholar database. The authors use the work of researchers and financial institutions to present a picture of the PayTech sector in Poland. The literature review also includes NBP reports and analyzes as well as opinions of experts in the field of finance and technology. Results of the research. The PayTech sector in Poland has great development potential due to the growing number of electronic payments and the planned expansion of the BLIK system to other countries. New technologies such as blockchain bring significant benefits to the PayTech sector, including data decentralization and increased transaction security. The PSD2 directive opened the financial market for the FinTech sector, which may increase the innovativeness of the PayTech sector and increase its competitiveness. Payment systems in Poland, such as BLIK, compete with traditional banks and may also have transnational potential. The increasing popularity of cashless payments in Poland is the result of the COVID-19 pandemic and the rising costs of using cash. Methodology. The methodology of the article is based on the analysis of the literature on the subject, mainly based on research available in the Google Scholar database. The authors use the work of researchers and financial institutions to present a picture of the PayTech sector in Poland. The literature review also includes NBP reports and analyzes as well as opinions of experts in the field of finance and technology. Results of the research. The PayTech sector in Poland has great development potential due to the growing number of electronic payments and the planned expansion of the BLIK system to other countries. New technologies such as blockchain bring significant benefits to the PayTech sector, including data decentralization and increased transaction security. The PSD2 directive opened the financial market for the FinTech sector, which may increase the innovativeness of the PayTech sector and increase its competitiveness. Payment systems in Poland, such as BLIK, compete with traditional banks and may also have transnational potential. The increasing popularity of cashless payments in Poland is the result of the COVID-19 pandemic and the rising costs of using cash.